Sexual Practices Among a Sample of Young Lesbian and Bisexual Women from Mexico: An Exploratory Study. Issue 2 (3rd April 2019) - Mendoza-Pérez, Juan Carlos; Ortiz-Hernández, Luis; Lozano-Verduzco, Ignacio
Abstract: Objective : To describe sexual practices in Mexican lesbian and bisexual women. Materials and method : An online survey was conducted with a nonprobabilistic sample of self-identified lesbian ( n  = 768) and bisexual ( n  = 371) women from the 32 states of Mexico. Results : Lesbians less frequently reported having had sex with a man than bisexual women. Preferred sexual practices with other women were external genital stimulation with fingers, internal genital stimulation with fingers, and oral genital stimulation. Most (∼80%) participants did not use protection to prevent sexually transmitted infections. Conclusions : Our results can inform the design of promotion and prevention programs in sexual health aimed at sexual minority women.